Enhancing Management Effectiveness of the Teacher Educational Program through Job Cards and Activity Control - Soesetio, Yuli; Ekawati, Ratna; Pratama, Bima Wahyu; Mayasari, Ervira; Putri, Lifa Rosiana (SAFE-Network, 2025)
The Teacher Professional Education Program (PPG) at Universitas Negeri Malang faces several managerial challenges, particularly in terms of timely implementation and financial accountability. This study aims to explore the impact of implementing job cards and activity control systems on improving the effectiveness of PPG program management. A qualitative approach with a case study design was employed. Data were collected through semi-structured interviews, participatory observation, and document analysis related to the implementation of PPG activities. Informants included the director of the postgraduate school, the administrative sub-coordinator of the postgraduate school, and part-time financial staff. Data analysis was conducted thematically using source, technique, and time triangulation to enhance the validity of the findings. The results indicate that job cards provide clarity regarding roles and scheduling of activities, while activity control systems promote consistency in reporting and adherence to established timelines. Both instruments contribute to the development of a more disciplined, transparent, and accountable management system. Furthermore, active involvement of all implementing units fosters a collaborative work culture and accelerates the achievement of program targets. This study contributes for the development of participatory and accountable education management systems.